SHAPING THE PROCESS OF PENETRATION IN THIN TARGETS - Chernokozhev, Plamen; Antonov, Anton; Dqnkov, Plamen (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
An analytic model is created describing the process of hitting thin targets. Mathematical expressions for determining the work for forming a stopper, for plastic expansion of the opening, work for friction and work done for heating are suggested.